Schillerian concepts present in the work Beatriz Cenci by Gonçalves Dias - Guimarães, Jéssica de Oliveira (Opiniães, 2019)
The objective of this article is to analyze the dialogue established by Gonçalves Dias with Friedrich Schiller, in developing his dramas, especially Beatriz Cenci. For this, the presentation of some philosophical concepts, developed by the German, will be presented, evidencing how are present in the Gonçalves’s work, as the idea of art and freedom. In addition, we will observe some points pointed out by Gonçalves Dias in his prologue to Leonor de Mendonça. This text is fundamental for the study of the Gonçalves’s drama, since it presents the author's objective in relation to the genre, reinforcing the author's dialogue with Schillerian ideas and with other thinkers, such as Victor Hugo, who also approaches the German when speaking of themes such as fatality, in addition to his conception of incisive truth, fundamental to the outcome of Gonçalves Dias's dramas.